DAMPAK GLOBALISASI TERHADAP PESERTA DIDIK DAN KUALITAS PENDIDIKAN DI LINGKUP SEKOLAH MENENGAH KEJURUAN - Rian Padkur Rohman; Edy Soesanto; Abdullah Ammar Robbani (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The era of globalization has become a reality that must be faced by the Indonesian people and nation. Changes that are taking place so quickly and the emergence of various challenges as a result of globalization must be faced and resolved properly. Education is inevitably involved in it and is required to be able to make a significant contribution. Industrial revolution 4.0 is the government's dream to build the Indonesian nation into a nation that is able to compete with other nations. This aims to improve the quality of human resources in Indonesia, by emphasizing awareness in education, one of them. The industrial revolution itself is the impact of the globalization process. Globalization is the opening of culture and the development of science in all parts of the world which until now have become dependent. Through education, students must take advantage of the positive impacts of globalization so that they can foster good learning behavior and be able to avoid its negative impacts. Good learning behavior can lead students to become superior individuals, and even have good qualities. The results of the research show that vocational schools, both public and private in Indonesia, are affected by the impact of globalization on students' learning behavior, which has greatly increased compared to before.